Bioelectrical impedance analysis in the assessment of pre-eclampsia - Berlit, Sebastian; Stojakowits, Marlene; Tuschy, Benjamin; Weiss, Christel; Leweling, Hans; Suetterlin, Marc; Kehl, Sven (Archives of Gynecology and Obstetrics, 2015)
Aim of this prospective investigation was to assess pre-eclampsia by bioelectrical impedance analysis (BIA).A total of 22 pre-eclamptic as well as matched (patients' age, gestational age, parity, gravidity) healthy pregnant women underwent whole body BIA on admission and then, pre-eclamptic patients, every 2 days until childbirth. For all measured BIA single values and their corresponding reference value mean, standard deviation, minimum and maximum were calculated to compare pre-eclamptic women with corresponding reference values. Furthermore a paired t test and an ANOVA of repeated measurements were performed to detect differences of intraindividual measurements. Subsequently an analysis of variance was accomplished to analyse general changes in the course of time of investigated patients, who were measured more than once.Except for the phase angle, BIA parameters of pre-eclamptic women compared to corresponding reference values were significantly different, suggesting an increase of total body water in pre-eclampsia. Repeated measurements did not reveal statistically significant intra- or interindividual differences in the course of time.Bioelectrical impedance analysis allows differentiating healthy from pre-eclamptic women. Further investigations are needed to analyse if BIA is capable to serve as a prognostic diagnostic tool in the detection of deterioration of pre-eclampsia.
EVALuna2:17641